2021
DOI: 10.3390/su13031263
|View full text |Cite
|
Sign up to set email alerts
|

Innovating with Nature: From Nature-Based Solutions to Nature-Based Enterprises

Abstract: Nature-based solutions (NBS) to address societal challenges have been widely recognised and adopted by governments in climate change and biodiversity strategies. Nevertheless, significant barriers exist for the necessary large-scale implementation of NBS and market development is still in its infancy. This study presents findings from a systematic review of literature and a survey on private sector agents in the planning and implementation of NBS, with the aim to identify them. In this study, we propose a typo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 61 publications
0
34
0
2
Order By: Relevance
“…These and other benefits, such as the aesthetic and the psychological value, leveraging social cohesion, and the reduction of health risks, are not fully captured by markets. Connecting Nature and other projects have shown the multiple benefits generated by nature-based enterprises involved in the implementation of NBS-both economic benefits (such as jobs and wealth creation) and non-economic benefits (such as environmental education or community engagement) [24]. In other words, the positive and negative externalities generated by NBS are not internalised by market prices [15].…”
Section: Role Value and Typologies Of Business Models For Nbsmentioning
confidence: 99%
See 1 more Smart Citation
“…These and other benefits, such as the aesthetic and the psychological value, leveraging social cohesion, and the reduction of health risks, are not fully captured by markets. Connecting Nature and other projects have shown the multiple benefits generated by nature-based enterprises involved in the implementation of NBS-both economic benefits (such as jobs and wealth creation) and non-economic benefits (such as environmental education or community engagement) [24]. In other words, the positive and negative externalities generated by NBS are not internalised by market prices [15].…”
Section: Role Value and Typologies Of Business Models For Nbsmentioning
confidence: 99%
“…Recently, the concept of 'business models for sustainability (BMfS) was introduced by several authors [22][23][24], while others proposed 'sustainable business model archetypes' [25]. These strands of literature propose the development of financially profitable value propositions that also radically reduce negative and/or create positive external effects for the natural environment and society [23].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, with clear policies, incentives, and strategies, the market will be able to deliver the solutions to match the needs. Kooijman et al [57] identified two types of organizations delivering NBS products and services: (i) nature-based enterprise (NBE), associated to an economic activity, and (ii) nature-based organization (NBO), not associated to economic activity. The main difference between them is that NBE "use nature as a core element of their product/ service offering for the planning, delivery, and/or stewardship of NBS and engage in economic activity" and NBO "use nature as a core element of their product/service offering for the planning, delivery, and/or stewardship of NBS but do not engage in economic activity."…”
Section: Green Roof Inclusion In Citiesmentioning
confidence: 99%
“…From their conclusions, there is a need of organizations that are able to deliver large-scale implementation of NBS and market development. Furthermore, the recognition of NBE as important actors to leverage NBS and to job creation is an important dimension for NBS inclusion in cities, which also applies in particular to green roof systems [57]. 5.…”
Section: Green Roof Inclusion In Citiesmentioning
confidence: 99%
“…Nature-based enterprises have been identified as critical actors in the supply chain of NBS [14,15]. Echoing and enhancing Kooijman et al [14], we define a NBE as: "An enterprise, engaged in economic activity, that uses nature sustainably as a core element of their product/service offering.…”
Section: Introductionmentioning
confidence: 99%